2020
DOI: 10.1111/mpp.12945
|View full text |Cite
|
Sign up to set email alerts
|

Recent insights into barley and Rhynchosporium commune interactions

Abstract: Rhynchosporium commune is the causal pathogen of scald in barley ( Hordeum vulgare ), a foliar disease that can reduce yield by up to 40% in susceptible cultivars. R. commune is found worldwide in all temperate growing regions and is regarded as one of the most economically important barley pathogens. It is a polycyclic pathogen with the ability to rapidly evolve new virulent strains in response to resistance genes deployed in commercial cultivars. Hence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 119 publications
(178 reference statements)
2
42
0
Order By: Relevance
“…In 18 families the resistance score is improved by more than 0.5 scoring units. Around 50 QTLs are described on 3H, most of them in the region of Rrs1 (reviewed in [68]). Rrs1 was linked repeatedly to marker MWG680 [20,26,39,69,70] and the marker 11_0315 is derived from the same SNP [22].…”
Section: Chromosome 3hmentioning
confidence: 99%
“…In 18 families the resistance score is improved by more than 0.5 scoring units. Around 50 QTLs are described on 3H, most of them in the region of Rrs1 (reviewed in [68]). Rrs1 was linked repeatedly to marker MWG680 [20,26,39,69,70] and the marker 11_0315 is derived from the same SNP [22].…”
Section: Chromosome 3hmentioning
confidence: 99%
“…Currently, there are multiple rhynchosporium resistance genes that are spread across all barley chromosomes, except 5H (Hanemann 2009;Zhang et al 2020). The identification of new resistance genes that can be introgressed into elite lines could help make a more robust resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The dotted line denotes a significance threshold of a p value < 0.0001 2008). Additionally, the region identified in 2HL has not had any QTLs associated with rhynchosporium resistance (Zhang et al 2020). However, Büttner et al (2020 have recently identified a QTL in a similar location on 5HL as the one found in this study, further suggesting a potential novel source of resistance.…”
Section: Discussionmentioning
confidence: 99%
“…nov. (formerly: R. secalis (Oudem.) J.J. Davis) (Zaffarano et al 2011) is one of the most important diseases worldwide (Avrova and Knogge 2012;Zhang et al 2020). The name R. graminicola Heinsen 1897 is also suggested to be used as a replacing synonym for R. commune due to its longer history (Crous et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…So far, 148 quantitative trait loci (QTL) for scald resistance have been reported in barley (reviewed in Zhang et al 2020) including the following major resistance genes (R-genes): Rrs14 on chromosome 1H, Rrs17 on 2H, Rrs1 and Rrs4 on 3H, Rrs16 on 4H, Rrs13 and Rrs18 on 6H, Rrs2, Rrs 12, Rrs15, on 7H. R. commune is a genetically highly diverse pathogen (Abang et al 2006;McDonald 2015), which emphasizes the importance of using partial resistance over single R-genes and also the need to find new resistance mechanisms to replace the ones that are already overcome by pathogen evolution.…”
Section: Introductionmentioning
confidence: 99%